Less : a novel - Greer, Andrew Sean (A Lee Boudreaux Book, Little, Brown and Company, 2017)
Receiving an invitation to his ex-boyfriend's wedding, Arthur, a failed novelist on the eve of his fiftieth birthday, embarks on an international journey that finds him falling in love, risking his life, reinventing himself, and making connections with the past.